2014
DOI: 10.1523/jneurosci.3520-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Induced Fever Is Mediated by IL-6 Receptors on Brain Endothelial Cells Coupled to STAT3-Dependent Induction of Brain Endothelial Prostaglandin Synthesis

Abstract: The cytokine IL-6, which is released upon peripheral immune challenge, is critical for the febrile response, but the mechanism by which IL-6 is pyrogenic has remained obscure. Here we generated mice with deletion of the membrane bound IL-6 receptor ␣ (IL-6R␣) on neural cells, on peripheral nerves, on fine sensory afferent fibers, and on brain endothelial cells, respectively, and examined its role for the febrile response to peripherally injected lipopolysaccharide. We show that IL-6R␣ on neural cells, peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 33 publications
3
78
2
2
Order By: Relevance
“…The present data confirm that prostaglandin production in brain endothelial cells is important for the febrile response (Engström et al, 2012;Wilhelms et al, 2014;Eskilsson et al, 2014a).…”
Section: Role Of Peripherally Produced Pge2 For the Febrile Responsesupporting
confidence: 87%
“…The present data confirm that prostaglandin production in brain endothelial cells is important for the febrile response (Engström et al, 2012;Wilhelms et al, 2014;Eskilsson et al, 2014a).…”
Section: Role Of Peripherally Produced Pge2 For the Febrile Responsesupporting
confidence: 87%
“…IL--1β, TNF--α and IL--6 have been shown to be responsible cytokines in the induction of fever, and where IL--1β seems to be dependent on IL--6 to induce fever 81,109 . Blood borne cytokines may act directly at sites lacking the blood--brain barrier, they might induce secondary cytokine production in hypothalamus or might be actively transported in there 81 .…”
Section: Fevermentioning
confidence: 99%
“…The critical role of the endothelial cells is further supported by the finding that mice lacking the membrane-bound receptor for IL-6 on brain endothelial cells show attenuated fever after LPS administration as well as a strong reduction of COX-2 expression in the brain [79]. Recently it was also shown that deleting COX-2 or mPGES-1 specifically in brain endothelial cells strongly attenuates the fever response after LPS injection [80].…”
Section: The Blood Brain Barriermentioning
confidence: 93%